KEANEKARAGAMAN JENIS TUMBUHAN HIAS DI GUNUNG SIBUATAN DESA NAGALINGGA KECAMATAN MEREK KABUPATEN KARO SUMATERA UTARA - Rizky Ananda; Kartika Manalu; Melfa Aisyah Hutasuhut (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2021)
This study aims to determine the diversity of species of plants that have the potential as ornamental plants in Mount Sibuatan, Nagalingga Village, Brand District, Karo Regency, North Sumatra. This study uses a single plot method by means of purposive sampling. The results of research that have been conducted at Mount Sibuatan, Nagalingga Village, Brand District, Karo Regency, North Sumatra, obtained 31 species, namely Amydrium humile Schott, Epipremnum pinnatum (L.) Engl, Pinnata sp, Dianella ensifolia (L.) Redout, Aspelnium nidus L, Asplenium normale D. Don, Sphaeropteris polypoda (Baker) RM Tryon, Calystegia sp, Tripterospermum trinerve Blume, Aeschynanthus pulcher (Blume) G. Don, Codonoboea crinita (Jack) CLLim, Hypnodendron sp, Huperzia phlegmaria (L.) Rothm, Medinilla beamanii Regalado, Anoectochilus longicalcaratus JJSm, Ceratostylis subulata Blume, Coelogyne xyrekes Ridl, Erythrodes blumei (Lindl.) Schltr, Mesophlebion motleyanum (Hook) Holttum, Freycinetia javanica Blume, Davallia denticulata (Burm.f.) pumila (Blume) Fern.Vill, Argostemma involucratum Hemsl, Argostemma parvifolium Benn, Mycetia angustifolia Ridl, Selaginella caudata (Desv.) Spring, Cayratia mollissima (Wall.) Gagnep, Gl obba marantina L and Hedychium cylincdricum Ridl. The Diversity Index of potential ornamental plants on Mount Sibuatan is categorized as medium with a value of 1.623, which is those with stable communities. The potential plant habitats for ornamental plants that are obtained are grouped into 3 types, namely habistus liana, terrestrial and epiphytic.Â